PELATIHAN BUNDA PENGASUH DETEKSI TUMBUH KEMBANG (BUSUH BIDEK TUMBANG) DI DAYCARE UNISA - Estri, Belian Anugrah; Satriyandari, Yekti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Childcare at daycare plays an essential role in supporting children’s growth and development, especially when parents have limited time. However, many caregivers still lack comprehensive knowledge of early detection of child development. This community service aimed to improve the knowledge and skills of caregivers at UNISA Daycare in conducting early detection using the Developmental Pre-Screening Questionnaire (KPSP). The methods included coordination, training, and developmental screening of 15 children. Results showed that all children had normal KPSP scores, although two had body weight below their age standard. Caregivers actively participated in the training and were able to conduct screening independently. This program highlights the importance of early detection in preventing developmental delays and is expected to be sustainably implemented at UNISA Daycare